Expression of potential stem cell-related markers in acute myeloid leukaemia cell lines and gene silencing effect of HOXA3 in THP-1 cells - Panneerselvan, Hindhuja (2021)
Leukamia is a type of malignancy which originates in the bone marrow where haematopoiesis takes place. Acute myeloid leukaemia (AML) is one subtype which is more common among adults. AML is a heterogeneous disease marked by poor prognosis, high disease-related mortality and frequent relapse. Leukemic stem cells (LSCs) may play a role in early relapse of the disease. However, the LSC phenotype and regulatory mechanism that confer a higher resistance of LSCs to treatment is still unclear. Characterization of LSC associated biomarkers in available AML cell lines and related control mechanisms will provide an opportunity to use these as disease models to understand the biological characteristics of LSC and its relation with treatment outcome. The aim of this study was to characterize the LSC by phenotype and function. RT-qPCR was used to analyze the gene expression levels of a limited number of published LSC biomarkers (ALDH, IL3RA, CLEC12A), 86 new identified genes and 37 unidentified genes (chromosome contig) from an earlier study as well as standard markers associated with early haematopoiesis (CD34 and CD38) and myelopoiesis (ANPEP/CD13, Siglec-3/CD33 and CD14) on myeloid leukaemia cell lines: K562, THP-1 and HL-60 and induced pluripotent cells from THP-1 (iPSC-THP- 1). Due to similarity in phenotype to human embryonic stem cells as reported, iPSCTHP- 1 cells were used as reference to identify the patterns of stem cell related markers. Flow cytometry method was used to confirm the phenotype of a selected number of these markers including ALDH, IL3RA/ CD123, CLEC12A/CD371, HOXA3, ENPP4, ANPEP/CD13, CD34, CD38 on the cell lines in addition to another myeloid leukaemia cell line, KG-1a and cord blood cell samples. HOXA3 from the poor prognosis library was selected for siRNA gene silencing study in THP-1. Lipofectamine 2000 reagent was used to transfect siRNAs into THP-1 and cells were allowed to incubate for 72 hours. Subsequently, intracellular and surface marker staining were performed using flow cytometry to determine the silencing effect of HOXA3 on THP-1 cell. All samples examined were positive for the combined CD13/CD14/CD33 markers confirming myeloid origin. The cell lines were double positive for CD34+CD38+except iPSC-THP-1 which were mainly CD34+CD38- and cord blood which were CD34+CD38low. Stem cell feature of iPSC-THP-1 was confirmed with positivity for ALDH, which was also expressed on HL-60, the most mature cell lines. IL3RA/CD123 was lower in iPSC-THP-1 and cord blood and higher in other cell lines but was absent in HL-60. Expression of CLEC12A/CD371 was also absent only in very early stem cells (iPSC-THP-1) and mature cells (HL-60) but expressed earlier in cord blood cells. ALDH+ expression appeared inverse to IL3RA/CD123 and CLEC12A/CD371. Based on these, predicted cells with decreasing stem cell characteristics were iPSC-THP-1, cord blood cells, other myeloid leukaemia cell lines (THP-1, K562, KG-1a) and HL-60. HOXA3 appeared to increase with cell immaturity with highest expression in iPSC-THP-1 (RT-qPCR result) followed by cord blood cells and THP-1 while ENPP4 was reversed and highly expressed on HL-60. Both were absent in K562. These two genes were selected from an earlier study from this group. Genes identified from RT-qPCR with potential for gene silencing study were HOXA3, SF3B1, NBPF15 and MTND5. THP-1 was selected as potential leukaemia stem cell line for further gene silencing with HOXA3. Gene silencing resulted in reduction in expression of HOXA3 as well as other markers (CD14, CD34, CD38, CD123 and CD371) post transfection. The CD34+CD38- phenotype was expressed only on very early stem cells (iPSC THP-1). The published stem cell biomarkers, ALDH was positive on iPSC-THP-1 but not CD123 and CD371 which appeared only in later progenitor cells. The combined expression of HOXA3+ENPP4+/- may be as useful as CD34+CD38- to use as cut-off to differentiate LSCs from early progenitor cells. Knockdown experiment with HOXA3 suggested its importance in maintaining stem cell character. These results require validation in primary AML samples.